Study of outcome of displaced calcaneal fractures by closed reduction and percutaneous internal fixation with multiple k wires and screws - Kharat, Akshay Ravindra; More, Dhananjay Eknathrao; Desai, Shrikant Sudamrao (International Journal of Research in Orthopaedics, 2023)
Background: Calcaneum is the largest of the tarsal bones and the largest bone of the foot. Calcaneum fracture account for 2% of all fracture of the body and 60% of all tarsal fractures. Many calcaneal fractures are work related as they result from a fall from height, especially in male age 35-45 years. In our study we treated the displaced calcaneal fracture with closed reduction and percutaneous fixation using multiple percutaneous K-wires and screw to evaluate their functional outcome. Methods: The study was conducted as a prospective study at the department of Orthopaedics, Dr. Shankarrao chavan Government Medical College, Nanded, India during the period January 2019 to June 2020. Thirty patients of 20 to 60 years, who underwent surgical fixation for displaced calcaneal fracture using multiple K wires and screws were followed up. Functional outcomes at six month follow up were assessed. Results: In this study we selected 30 patients with displaced calcaneal fracture admitting in our institute. All patients underwent operative procedure in the form of multiple k wire and cc .screws by percutaneous approach Out of all 30 patients treated with this method had shown excellent results with minimal postoperative complications. Conclusions: The study with percutaneous K wires and screws for displaced calcaneal fractures showed very good functional outcome. Although it was not free of complications, our study has shown very good results. Technique involve in our study is less invasive, with minimum blood loss, less operative time without soft tissue stripping.